Enhancement mechanism of polyoxyethylene nonyl phenyl ether on the bioleaching of chalcopyrite. (1st November 2021) - Zhang, Hao; Wei, Dezhou; Liu, Wengang; Hou, Duanxu; Zhang, Ruiyang
Graphical abstract: Highlights: NP-15 was used to improve the bioleaching efficiency of chalcopyrite. NP-15 has proven to be a high-efficiency bioleaching agent. The oxidation of elemental sulfur by the bacteria was enhanced with NP-15. The wettability of chalcopyrite was improved by NP-15. Abstract: Chalcopyrite is the most abundant copper-bearing mineral in nature. Due to technological limitations, a large amount of low-grade chalcopyrite is discarded, which causes a large waste of resources and a series of environmental problems. Bioleaching is a low-consumption technology that plays an important role in treating low-grade minerals. However, the leaching efficiency of chalcopyrite is too low for industrial production. This study proposes the use of polyoxyethylene nonyl phenyl ether (NP-15) to improve the bioleaching efficiency of chalcopyrite. The effects of concentration and adding time of NP-15 on copper extraction were investigated. After 30 days bioleaching, the copper concentration in the leaching solution was 930.91 mg/L with the addition of 20 mg/L of NP-15. In contrast, the copper concentration was observed to be 385.62 mg/L in the absence of NP-15. The optimum adding time was the 6th day after the start of the bioleaching process. The analysis of the results of X-ray diffraction (XRD), Raman spectroscopy, and the electrochemical tests revealed that the presence of NP-15 was beneficial to reduce the deposition of elemental sulfur on the chalcopyrite surface. Moreover, NP-15 promoted the oxidation of elemental sulfur by Acidithiobacillus ferrooxidans . The contents of elemental sulfur and polysulfide in the passivation layer were reduced. Additionally, NP-15 reduced the surface tension of the leaching solution, which was beneficial for improving the contact between the leaching solution and chalcopyrite surface. Thus, the bioleaching efficiency was improved. This study provides a reference for the application of surfactants to enhance the bioleaching of chalcopyrite ores.